Pengaruh Literasi Keuangan Dan Perilaku Keuangan Terhadap Minat Investasi Mahasiswa - Kecia Nenoliu; Ari Data; Agustina Butar-Butar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of financial literacy and financial behavior on students' investment interest. The background of this study is based on the low investment interest of students, indicated by the dominance of neutral to disagree responses on various investment interest indicators. The research method used is a quantitative approach with data collection techniques through questionnaires. The population in this study were students of the Economics Education Study Program at Nusa Cendana University, class of 2022-2025, with a sample of 209 respondents determined using a purposive sampling technique. Data analysis was performed using the classical assumption test, multiple linear regression, t-test, F-test, and coefficient of determination test. The results showed that financial literacy has a positive and significant effect on investment interest with a coefficient value of 0.539 and a significance of 0.000. Financial behavior also has a positive and significant effect on investment interest with a coefficient value of 0.335 and a significance of 0.000. Simultaneously, financial literacy and financial behavior have a significant effect on investment interest with a calculated F value of 159.661 and a significance of 0.000. Furthermore, the coefficient of determination test results showed an R-square value of 0.608, indicating that the two independent variables were able to explain 60.8% of the variation in investment interest, while the remainder was influenced by factors outside the study. Therefore, it can be concluded that improving financial literacy and financial behavior are important factors in increasing students' investment interest.Keywords: Financial Literacy, Financial Behavior, Consumer Behavior